Image quality and radiation dose of lower extremity CT angiography using 70 kVp, high pitch acquisition and sinogram-affirmed iterative reconstruction. - Li Qi; Felix G Meinel; Chang Sheng Zhou; Yan E Zhao; U Joseph Schoepf; Long Jiang Zhang; Guang Ming Lu (PLoS ONE, 2014)
OBJECTIVES: The purpose of this study was to assess image quality and radiation dose of lower extremity CT angiography (CTA) with 70 kVp, high pitch acquisition and sinogram-affirmed iterative reconstruction (SAFIRE). METHODS: Lower extremity CTAs were performed on 44 patients: 22 patients were examined using protocol A (120 kVp, pitch of 0.85 and 120 ml of contrast agent on a first-generation dual-source CT) (120 kVp group) and 22 patients were evaluated with protocol B (70 kVp, pitch of 2.2 and 80 ml of contrast agent on a second-generation dual-source CT) (70 kVp group). Images from the 120 kVp group were reconstructed with filtered back projection (FBP) and images from the 70 kVp group with SAFIRE. The attenuation, image noise, signal-to-noise ratio (SNR) and contrast-to-noise ratio (CNR) were calculated. Two radiologists subjectively assessed image quality of lower extremity arteries, plantar arterial enhancement and venous contamination of all patients. Radiation dose was compared between the two groups. RESULTS: Higher mean intravascular attenuation was obtained in the 70 kVp group (70 vs. 120 kVp group, 555.4 ± 83.4 HU vs. 300.9 ± 81.4 HU, P<0.001), as well as image noise (20.0 ± 2.8 HU vs. 17.5 ± 3.2 HU, P = 0.010), SNR (32.0 ± 7.0 vs. 19.1 ± 6.9, P<0.001) and CNR (28.1 ± 6.6 vs 15.9 ± 6.3, P<0.001). No difference in subjective image quality and plantar arterial enhancement was found between 120 kVp group and 70 kVp group (all P>0.05). The venous contamination score was 1.5 ± 0.8 for 120 kVp group while no venous contamination was found in 70 kVp group. The inter-observer agreement was moderate to good for both groups (0.515∼1, P<0.001). The effective dose was lower in 70 kVp group (0.3 ± 0.1 mSv) than in 120 kVp group (1.6 ± 0.7 mSv)(P<0.001). CONCLUSIONS: Lower extremity CTA using 70 kVp, high pitch acquisition and SAFIRE, except increasing imaging noise, allows for lower radiation dose and contrast material volume without compromising image quality.